1994
DOI: 10.1088/0953-8984/6/40/014
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear magnetic resonance study of superionic conductors with tysonite structure

Abstract: The fluorine mobility in single crystals of the anion-deficient solid solution La1-xSrxF3-x (x=0, 0.001, 0.003, 0.01, 0.03, 0.05 or 0.16) with the tysonite structure has been studied in the temperature range of 130-520 K by 19F NMR. Different modes of ionic motion were identified and the leading mechanism of ionic diffusion has been suggested. The influences of temperature and fluorine vacancy concentration on the ionic mobility in tysonite have been investigated. In all crystals, fluorine diffusion begins in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 14 publications
5
55
0
1
Order By: Relevance
“…The single crystals of La,_ X SrF3 _x (x = 0; 0.03) were the same as studied in earlier works [9,16]. Their quality was checked optically and using Laue X-ray diffraction.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The single crystals of La,_ X SrF3 _x (x = 0; 0.03) were the same as studied in earlier works [9,16]. Their quality was checked optically and using Laue X-ray diffraction.…”
Section: Methodsmentioning
confidence: 99%
“…This is particularly important when more than one motional process are activated, a situation found in superionic conductors of the type La 1 _XSrF3 _x with tysonite structure [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The particular dipole-dipole interactions are modulated by jumps of the fluorine ions between equivalent (F A -F A , F B -F B ) and non-equivalent (F A -F B ) lattice sites. Important information on the dynamics of the fluorine ions in LaF 3 has been gained from the analysis of the fluorine lineshape [16,17], fluorine diffusion measurement by NMR gradient techniques [18] and some earlier relaxation studies performed at high magnetic field [14,19]. In [16,17] the two different fluorine subsystems have been clearly identified in the NMR spectrum by their chemical shifts.…”
Section: Mechanisms Of Fluorine Spin Relaxation In Laf 3 Crystalsmentioning
confidence: 99%
“…Important information on the dynamics of the fluorine ions in LaF 3 has been gained from the analysis of the fluorine lineshape [16,17], fluorine diffusion measurement by NMR gradient techniques [18] and some earlier relaxation studies performed at high magnetic field [14,19]. In [16,17] the two different fluorine subsystems have been clearly identified in the NMR spectrum by their chemical shifts. It has been observed that fast fluorine motion within the F A sublattice leads to a narrowing of the corresponding resonance line, while the F B line stays broad until it collapses with the faster one.…”
Section: Mechanisms Of Fluorine Spin Relaxation In Laf 3 Crystalsmentioning
confidence: 99%